Investigation on the Settlement of High Rockfill Embankment Using Centrifuge Tests - Jing, Hong Jun; Gou, Ming Jie; Zhang, Yan Qing; Song, Ki-IL (Frontiers in Physics, 2021)
In this paper, a more than 50 m high rock fill embankment of the second-class road reconstruction project from Xunyang to Ankang of the national road 316 in Shaanxi, China, was selected as the research object. A set of centrifuge tests was performed to study the deformation laws and the impact on the surrounding environment of high rock fill embankment. The test results showed that: (i) the high rock fill embankment was stable during construction and operation; (ii) during construction, settlement occurred at the embankment top, and uplift occurred at the slope foot. Moreover, the deformation at the top was greater than that at the slope foot, and the deformations both the top and the slope toe, reached maximum value at the end of construction; (iii) during operation, the settlement at the embankment top continued, and it changed rapidly at the start of operation. And then, the rate of settlement slowed down and reached a steady state finally. The deformation of the slope foot was very small; and (iv) in terms of the deformation range, the construction and long-term operation of the high rock fill embankment will not affect the nearby railway and water area. This study can also provide basis and reference for the design and construction of similar project in mountain areas.